The multidimensional analysis of the private equity funds in Central and Eastern Europe - Dutt, Andrew; Dudzich, Viktar; Šíma, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
This thesis aims to provide the reader with an understanding of value creation in private equity investing. It seeks to show, on specific examples, how private equity funds can improve a company’s financial indicators and thus its value. The theoretical part of this thesis consists of three main chapters, each describing a different aspect of private equity investing. The first serves as an introduction to private equity; the second describes the global private equity market; and the third delves into specific methods utilized by private equity funds to acquire companies and create value. In the empirical part, the methods of value creation by funds are put to the test via two case studies, one focusing on an industrial services company and the other on a software company. Both case studies confirmed that the theoretical methods of value creation are also successfully utilized in practice.
Vedoucí práce: Viktar Dudzich
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses